(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Dye waste water are one of the most problematic pollutants because they can be easily identify by the human eye the dye waste water not easily biodegradable. Colour present even at a very low concentration of 1mgl will be easily visible. Textile industry produced a large amount of highly coloured waste water containing varieties of dyes in different concentration. Treatment of textile dying industries has been a challenging task yet now in many part of the world problem in the treatment of textile dye industries are majorly the removal of pollutants like colour, BOD, COD AND TDS. In the textile industry there are different type of process are used. The effluents resulting from these process differ greatly in composition. Characterisation of textile dye industry effluents is of great importance for the separate treatment of process streams. Different Colour is released in a greater percentage from dying process of textile industries. Coloured waste water from dye industries is rated as the most polluted is almost all industries sector. The review paper is about which type of treatments are performed and what type of treatment are economical for the treatment of dye waste water. In the review paper the major consideration of the economical treatment, because there are many different process and different methods are available but some method are costlier and some are economical. Economical methods are suitable for most of the small as well as large industry. The reviews provide an overview of the types of method and low cost treatment method.